Journal of Early Modern Christianity (De Gruyter, 2014)
The Journal of Early Modern Christianity (JEMC) intends to contribute to interdisciplinary, interconfessional, and comparative research on early modern Christianity. The journal bears out its interdisciplinary character by including a variety of relevant disciplines, such as church history, social history, cultural history, art history, literary history, history of ideas, history of music and archeology.